RURAL-URBAN PRICE TRANSMISSION AND MARKET INTEGRATION OF SELECTED HORTICULTURAL CROPS IN OYO STATE, NIGERIA (2013)
The majority of agricultural markets in African countries are inefficient and poorly integrated. This study therefore assessed the level of market integration and the trend analysis of selected vegetable crops in Oyo State. It also identified the leading market between rural and urban markets in Oyo state. Secondary data on the prices of fresh tomato, onion, chilli pepper, sweet pepper, and fresh pepper (2003–2011) were obtained from Oyo State Agricultural Development Programme and were analysed using trend analyses, Augmented Dickey-Fuller (ADF) test, Granger causality test and index of market concentration. Results showed that the prices of onion, chilli pepper and fresh pepper were non-stationary in their various level forms but stationary at first difference; while prices of fresh tomato and sweet pepper in urban markets were stationary at their level form at probability of 5% respectively. The indices of market concentration for onion, sweet pepper, fresh pepper, chilli pepper were less than one suggesting high short-run market integration, whereas fresh tomato achieved low short-run market integration. Further, urban markets were the leading markets for onion, chilli pepper and sweet pepper, while rural markets were the leading markets for fresh tomato and fresh pepper.